First observation of the KS → π0γ γ decay - Lai, A; Marras, D; Batley, JR; Dosanjh, R; Gershon, T; Kalmus, G; Lazzeroni, C; Munday, D; Olaiya, E; Parker, M; White, T; Wotton, SA; et al. (2004)
Using the NA48 detector at the CERN SPS, 31 KS → π 0γγ candidates with an estimated background of 13.7 ± 3.2 events have been observed. This first observation leads to a branching ratio of BR(KS → π0γγ) z>0.2 = (4.9 ± 1.6stat ± 0.9 syst) × 10-8 in agreement with Chiral Perturbation Theory predictions. © 2003 Elsevier B.V. All rights reserved.